1989
DOI: 10.1016/0735-1097(89)90504-4
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular shape, afterload and survival in idiopathic dilated cardiomyopathy

Abstract: Because idiopathic dilated cardiomyopathy is characterized by elevated wall stress and a more spherical left ventricle, the relations among shape, afterload and survival were examined. Thirty-six patients with cardiomyopathy were prospectively studied by two-dimensional echocardiography. Data included echocardiographic short- and long-axis cavity dimensions, their ratio and, with cuff systolic blood pressure, meridional and circumferential end-systolic stress and their ratios. Survivors (n = 16) were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
9

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(96 citation statements)
references
References 16 publications
1
86
0
9
Order By: Relevance
“…[52][53][54] Although some investigators currently view LV remodeling simply as the end-organ response that occurs after years of exposure to the deleterious effects of long-term neurohormonal stimulation, others have suggested that LV remodeling may contribute independently to the progression of heart failure. 52,55 Although a complete discussion of the complex changes that occur in the heart during LV remodeling is well beyond the intended scope of this brief review, it is worth emphasizing that the process of LV remodeling extends to and affects importantly the biology of the cardiac myocyte, the volume of myocyte and nonmyocyte components of the myocardium, and the geometry and architecture of the LV chamber (Table 3).…”
Section: Remodeling As a Cause Of Disease Progression In Heart Faimentioning
confidence: 99%
“…[52][53][54] Although some investigators currently view LV remodeling simply as the end-organ response that occurs after years of exposure to the deleterious effects of long-term neurohormonal stimulation, others have suggested that LV remodeling may contribute independently to the progression of heart failure. 52,55 Although a complete discussion of the complex changes that occur in the heart during LV remodeling is well beyond the intended scope of this brief review, it is worth emphasizing that the process of LV remodeling extends to and affects importantly the biology of the cardiac myocyte, the volume of myocyte and nonmyocyte components of the myocardium, and the geometry and architecture of the LV chamber (Table 3).…”
Section: Remodeling As a Cause Of Disease Progression In Heart Faimentioning
confidence: 99%
“…[23][24][25] Although some investigators currently view LV remodeling simply as the end-organ response that occurs following years of exposure to the toxic effects of long-term neurohormonal stimulation, others have suggested that LV remodeling may contribute independently to the progression of heart failure. 23 Given the potential central importance of LV remodeling in the progression of heart failure, the following section will focus on the basic cellular and molecular mechanisms responsible for this process.…”
Section: Remodeling: Cause or Consequence Of Heart Failure?mentioning
confidence: 99%
“…In dilated cardiomyopathy, those patients with the most spherical ventricles demonstrate decreased survival. 6 Lamas er al. analyzed LV shape in 699 patients following MI, and noted that systolic sphericity index predicted mortality independent of ejection fraction.?'…”
Section: Discussionmentioning
confidence: 99%